Prevalence and phylogenetic analysis of human enteric emerging viruses in porcine stool samples in the Republic of Korea - Yeo, Daseul; Hossain, Md. Iqbal; Jung, Soontag; Wang, Zhaoqi; Seo, Yeeun; Woo, Seoyoung; Park, Sunho; Seo, Dong Joo; Rhee, Min Suk; Choi, Changsun (Frontiers in Veterinary Science, 2022)
Emerging infectious diseases (EID) in humans and animals are proving to be a serious health concern. This study investigated the prevalence of emerging or re-emerging human enteric viruses in porcine stools and swabs. Eleven enteric EID viruses were selected as target viruses for the current study and ranked based on their impact on public health and food safety: enterovirus (EV), hepatitis E virus, norovirus GI and GII, sapovirus (SaV), adenovirus (AdV), astrovirus, rotavirus, hepatitis A virus, aichivirus, and bocavirus. Using real-time RT-PCR or real-time PCR, EID viruses were detected in 129 (86.0%) of 150 samples. The most prevalent virus was EV, which was detected in 68.0% of samples, followed by AdV with a detection rate of 38.0%. In following sequencing and phylogenetic analyses, 33.0% (58/176) of the detected viruses were associated with human enteric EID viruses, including AdV-41, coxsackievirus-A2, echovirus-24, and SaV. Our results show that porcine stools frequently contain human enteric viruses, and that few porcine enteric viruses are genetically related to human enteric viruses. These findings suggest that enteric re-emerging or EID viruses could be zoonoses, and that continuous monitoring and further studies are needed to ensure an integrated “One Health” approach that aims to balance and optimize the health of humans, animals, and ecosystems.